2012
DOI: 10.1021/jo300263k
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Dimerization of (E)- and (Z)-2-Propenylsesamol with O2 in the Presence and Absence of Laccases and Other Catalysts: Selective Formation of Carpanones and Benzopyrans under Different Reaction Conditions

Abstract: The oxidative dimerization of 2-propenylsesamol to carpanone with O(2) as the oxidant, which probably proceeds as a domino phenol oxidation/anti-β,β-radical coupling/intramolecular hetero Diels-Alder reaction, can be efficiently catalyzed by laccases. Experiments with laccases and other catalysts like a Co(salen) type catalyst and PdCl(2) clearly demonstrate that the diastereoselectivity of the carpanone formation does not depend on the catalyst but on the double-bond geometry of the substrate. With (E)-2-prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 72 publications
0
37
0
Order By: Relevance
“…Since a pioneering study the oxidative dimerization of 2‐propenylsesamol ( 107 ) to carpanone ( 109 a )175 has received considerable attention. Recently, the coupling of 107 to 109 a , which probably proceeds as a domino phenol oxidation/anti‐β,β‐radical coupling/intramolecular hetero Diels–Alder reaction, was found to be efficiently catalyzed by laccases using O 2 as the oxidant 176. Experiments with laccases and other catalysts like a Co II salen and PdCl 2 clearly demonstrate that the diastereoselectivity of the carpanone formation does not depend on the catalyst but on the double bond geometry of the substrate.…”
Section: Oxidation Of Activated Sp3 Ch Bonds With O2mentioning
confidence: 99%
“…Since a pioneering study the oxidative dimerization of 2‐propenylsesamol ( 107 ) to carpanone ( 109 a )175 has received considerable attention. Recently, the coupling of 107 to 109 a , which probably proceeds as a domino phenol oxidation/anti‐β,β‐radical coupling/intramolecular hetero Diels–Alder reaction, was found to be efficiently catalyzed by laccases using O 2 as the oxidant 176. Experiments with laccases and other catalysts like a Co II salen and PdCl 2 clearly demonstrate that the diastereoselectivity of the carpanone formation does not depend on the catalyst but on the double bond geometry of the substrate.…”
Section: Oxidation Of Activated Sp3 Ch Bonds With O2mentioning
confidence: 99%
“…The Beifuss group has also done extensive studies of oxidation of the cis and trans carpanone monomer and showed the diastereomeric outcomes under different oxidative conditions. With the trans starting material, the diastereomer corresponding to natural carpanone is formed almost exclusively . Recently, an automated flow reactor has been utilized to synthesize carpanone as well as other members of the benzoxanthenone scaffold .…”
Section: Figurementioning
confidence: 99%
“…Notably, the major product ( 2 ) arose from an unexpected exo Diels‐Alder reaction after the initial C−C dimerization. The structure and spectroscopic properties of 2 were determined based on prior studies by the Beifuss group . DFT calculations (B3LYP/6‐31G) reveal that the endo product ( 1 ) is 9.1 kcal/mol more stable than the exo product ( 2 ) in terms of free energy (see SI for details).…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations